Study of Bioecological Properties of Ginger Plant from Medicinal Plants - Rashidov Negmurod Elmurodovich; Allakulov Hasan Anvarovich (International Journal on Integrated Education, 2022)
Useful properties of ginger, its structure, importance in folk medicine, composition and valuable properties of ginger oil. The production of ginger oil, which is widely used in pharmacology, aromatherapy, cosmetics and homeopathy, occupies a special place among all types of ginger products.. In this article we will talk about the structure and medicinal properties of ginger.